2020
DOI: 10.1186/s12966-020-00939-2
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of obesogenic behaviours and family rules according to family structure in European children

Abstract: Background: There has been an increase in children growing up in non-traditional families, such as single-parent and blended families. Children from such families have a higher prevalence of obesity and poorer health outcomes, but research on the relationship with obesogenic behaviours is limited. Objectives: Therefore, the aim of this study was to investigate whether there are associations between family structures and obesogenic behaviours and related family rules in European children and adolescents. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 65 publications
(73 reference statements)
1
26
1
1
Order By: Relevance
“…Stahlmann et al observed that children from single-parent families reported longer hours of television consumption (p < 0.001) [18]. In our study, no signi cant difference was observed in this regard (p = 0.476).…”
Section: Discussioncontrasting
confidence: 66%
“…Stahlmann et al observed that children from single-parent families reported longer hours of television consumption (p < 0.001) [18]. In our study, no signi cant difference was observed in this regard (p = 0.476).…”
Section: Discussioncontrasting
confidence: 66%
“…Lower socioeconomic status (SES) is also associated with less physical activity [22], less screentime [27], and poorer sleep [28,29]. And recently, the family structure (e.g., living with both parents or single parent) has also been shown to be associated with screen time [30]. Fewer girls and fewer older adolescents seem to meet all 24-hour movement recommendations compared to boys and younger peers in the United States [21], while age was also inversely related to meeting all the guidelines simultaneously among Canadian adolescents [20].…”
Section: Introductionmentioning
confidence: 99%
“…An observational cohort study of 699 American children aged 6 to 11 years and their parents showed a prevalent use of encouragement/modeling and restrictive feeding practices and a high availability of low-calorie/nutrient-dense foods in the home, and other parenting and food availability measures were near the middle of the possible score range [20]. The Above studies agreed that compared to permission pattern, more families restricted children's eating Undoubtedly, the potential impact of FFE on children's food choice and diet quality is particularly relevant [23,[27][28][29][30][31]. A systematic review (14 studies published between 1994 and 2017) indicated that family environmental factors (household food availability, caregivers' nutritional knowledge and family income) were consistently associated with children's food consumption and micronutrient intake [22].…”
Section: Discussionmentioning
confidence: 77%